Improving rate capability and reducing over-potential of lithium-oxygen batteries through optimization of Dimethylsulfoxide-N/N-dimethylacetamide mixed electrolyte. (20th July 2017) - Chen, Chunguang; Li, Liangyu; Su, Junming; Zhang, Congcong; Chen, Xiang; Huang, Tao; Yu, Aishui
Abstract: Although dimethylsulfoxide (DMSO) solvent has been widely researched in rechargeable lithium-oxygen (Li-O2 ) batteries, high polarization voltage and low rate capability limited its application. In this work, we reported a DMSO-based electrolyte system by adding N, N-dimethylacetamide (DMA) to adjust its physical and electrochemical properties. The ionic conductivity, viscosity, oxygen solubility and diffusion coefficient of the mixed electrolytes as well as their electrochemical performance in Li-O2 batteries are researched. The electrochemical tests show that the optimized DMSO/DMA volume ratio is 30 to 70 based on the rate performance and polarization voltage of the cell. Compared with that of the pure DMSO-based electrolyte, the cell with the mixed electrolyte shows improved rate capability and reduced charge-discharge over-potential. When increasing current density from 0.2 to 0.5 mA cm −2, the capability retention improves from 32% to 59%. Meanwhile, the charge-discharge voltage gap drops from 1.4V to 0.9V at a current density of 0.2 mA cm −2 . The improved electrochemical performance could be attributed to low viscosity, high oxygen solubility and diffusion coefficient as well as the low charge-transfer resistance with the mixed electrolyte.